2010
DOI: 10.1161/circheartfailure.109.903849
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Soluble Corin in Patients With Heart Failure

Abstract: Background-Corin is a transmembrane protease that processes natriuretic peptides in the heart. Like many membrane proteins, corin is shed from the cell surface. Methods and Results-In this study, we obtained plasma samples from healthy controls and patients with heart failure (HF) and acute myocardial infarction. Soluble corin levels in plasma were measured by an ELISA method. In healthy adults (nϭ198), plasma corin levels were 690 pg/mL (SD, 260 pg/mL). The corin levels did not differ significantly among diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
150
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 136 publications
(168 citation statements)
references
References 47 publications
(45 reference statements)
16
150
2
Order By: Relevance
“…The 6 NT-proBNP immunoassays are named according to the first amino acid that the capture antibody binds to on the NT-proBNP molecule and the last amino acid that the detection antibody binds to on the NT-proBNP molecule of 1-76 amino acids: NT-proBNP 1-20 (5B6 1-12 and 13G12 [13][14][15][16][17][18][19][20] ); NT-proBNP (18H5 [13][14][15][16][17][18][19][20] and 11D1 28 -45 ); NTproBNP (5B6 [1][2][3][4][5][6][7][8][9][10][11][12] and 11D1 28 -45 ); NT-proBNP 28 -76 (11D1 28 -45 and 28F8 67-76 ); NT-proBNP (18H5 [13][14][15][16][17][18][19][20] and 28F8 67-76 ); NTproBNP 1-76 (5B6 [1][2][3][4][5][6][7][8][9][10][11][12] and 28F8 67-76 ). Each NTpr...…”
Section: Plasma Nt-probnp Alphalisa Immunoassaysmentioning
confidence: 99%
“…The 6 NT-proBNP immunoassays are named according to the first amino acid that the capture antibody binds to on the NT-proBNP molecule and the last amino acid that the detection antibody binds to on the NT-proBNP molecule of 1-76 amino acids: NT-proBNP 1-20 (5B6 1-12 and 13G12 [13][14][15][16][17][18][19][20] ); NT-proBNP (18H5 [13][14][15][16][17][18][19][20] and 11D1 28 -45 ); NTproBNP (5B6 [1][2][3][4][5][6][7][8][9][10][11][12] and 11D1 28 -45 ); NT-proBNP 28 -76 (11D1 28 -45 and 28F8 67-76 ); NT-proBNP (18H5 [13][14][15][16][17][18][19][20] and 28F8 67-76 ); NTproBNP 1-76 (5B6 [1][2][3][4][5][6][7][8][9][10][11][12] and 28F8 67-76 ). Each NTpr...…”
Section: Plasma Nt-probnp Alphalisa Immunoassaysmentioning
confidence: 99%
“…NT-proBNP is an inactive peptide produced in an equimolar ratio together with BNP by action of some cellular or circulating proteolytic enzymes (such as corin and furin) on the precursor pro-hormone (proBNP) (Figure 2) [1,14,[24][25][26][27][28]. As a result, NT-proBNP assay is not a reliable index of the biological (natriuretic) activity of cardiac endocrine system in severe HF because the concentration of less active peptides in patients with severe HF (such as NT-proBNP and proBNP) is greatly higher than that of the active peptide BNP (Figure 1) [1,[29][30][31][32][33].…”
Section: Groupmentioning
confidence: 99%
“…For the first time, Lewis et al [53] were able to set up an ELISA method that measures BNP in plasma without interference by proBNP. This two-site ELISA uses a specific polyclonal antibody that recognizes the amino-terminal end of BNP 1-32 and does not cross-react with proBNP, in conjunction with a C-terminal antibody, which recognizes BNP [26][27][28][29][30][31][32] . Detection by this assay requires both aminoterminus and carboxy-terminus of BNP to be intact.…”
Section: Quality Specifications For An Accurate Bnp Assaymentioning
confidence: 99%
“…If so, circulating soluble corin is speculated to be associated with age-related disorders. Circulating corin could be measured by enzyme-linked immunosorbent (ELISA) assays [6,[8][9][10]. To date, some small sampled case-control studies have examined circulating soluble coirn and found that corin in the circulation was decreased in osteoporosis [11], acute coronary syndrome [12], and heart failure [12] but increased in pregnant hypertension [13].…”
mentioning
confidence: 99%